Dealing with mass death in disasters and pandemics: Some key differences but many similarities - Scanlon, Joseph (Disaster Prev Manag, 2011)
PURPOSE: There are many differences in how authorities handle the dead during mass death incidents involving disasters and pandemics. These differences would suggest that planning for a disaster death and planning for a pandemic death should be done separately. This may be true to some extent, however, there are many similarities between the two that this article will seeks to examine. The main objective of this study is to show that planning for both disasters and pandemics should either be done by a single entity that coordinates both types of responses, or by agencies that communicate closely and frequently. DESIGN/METHODOLOGY/APPROACH: This study compared mass death incidents predominantly within the Canadian historical record, including disasters and pandemics. It took a specific look at the influenza pandemic of 1918 in North America and how the dead were handled. FINDINGS: Both disasters and pandemics offer unique challenges in handling the dead and documenting the incident. In a pandemic the cause of death is usually clear, while in a disaster it is not always understood. However, the similarities they hold in common must not be overlooked. They will involve immense and complicated amounts of paperwork, cause a shortage of supplies (be it medical, food or otherwise) and create the need for assistance. ORIGINALITY/VALUE: The research finds that though disasters and pandemics are often handled differently by the various agencies involved, they should be treated alike and dealt with in the same manner.